Antecedents of life satisfaction and the mediating effects of resilience: a study of working adults from the economic perspective - Bee, Kai Ying (2022)
The Malaysian government has recently targeted to achieve the status of high-income nation with better quality of life in the year 2025. Apparently, life satisfaction in Malaysia is still low, especially for those aged 20-39 years old. Therefore, this study aims to examine the determinants of life satisfaction among working adults aged 20-39 years old. In addition, this study also attempts to explore whether the resilience can mediate the relationship between determinants and life satisfaction. Data were collected from 384 respondents through self-administrative questionnaires. The SmartPLS Version 3.0 was used to perform the Partial Least Square of Structural Equation Modelling (PLS-SEM). In line with this, the results provide two notable findings. First of all, working adults’ financial literacy is found to provide a positive impact on their life satisfaction. Financial literacy enables individuals to better allocate their lifetime resources and persist with the daunting process of financial management. As a result, their ability in their money management would increase their life satisfaction. Secondly, resilience is found to mediate the relationship between physical health status and life satisfaction. Resilience is one of the factors of enhancing health awareness that causes a quick response to change the health behaviour to cope with the stress in having a good healthy life. As a consequence, those with good health status could have a relatively low depression rate and increase work productivity, which contributes to satisfaction in their life. Based on the findings, this study suggests that the Malaysian Financial Planning Council could further improve their courses to enhance the financial knowledge, financial attitude and training financial management behavior among working adults. In addition, the government is suggested to provide effective psychological interventions in the workplace. This includes promoting primary care prevention of physical ill-health among working adults in the country for the improvement of their life satisfaction.